2010
DOI: 10.1002/cssc.201000114
|View full text |Cite
|
Sign up to set email alerts
|

Can Metal–Organic Framework Materials Play a Useful Role in Large‐Scale Carbon Dioxide Separations?

Abstract: Metal-organic frameworks (MOFs) are a fascinating class of crystalline nanoporous materials that can be synthesized with a diverse range of pore dimensions, topologies, and chemical functionality. As with other well-known nanoporous materials, such as activated carbon and zeolites, MOFs have potential uses in a range of chemical separation applications because of the possibility of selective adsorption and diffusion of molecules in their pores. We review the current state of knowledge surrounding the possibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
435
1
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 576 publications
(452 citation statements)
references
References 165 publications
(157 reference statements)
10
435
1
6
Order By: Relevance
“…As shown in Fig. 5 2 , respectively. The demonstrated PAF materials promise a potential application in gas separations with high efficiency.…”
Section: Article Nature Communications | Doi: 101038/ncomms5260mentioning
confidence: 74%
See 1 more Smart Citation
“…As shown in Fig. 5 2 , respectively. The demonstrated PAF materials promise a potential application in gas separations with high efficiency.…”
Section: Article Nature Communications | Doi: 101038/ncomms5260mentioning
confidence: 74%
“…E fficient separations of light gases (H 2 , N 2 , O 2 , CO 2 and CH 4 ) are of great concern because most of them are very important raw ingredients in the chemical and petrochemical industry 1,2 . At present, air separation employing cryogenic distillation, as an energy-intensive method, needs to progress urgently 3 .…”
mentioning
confidence: 99%
“…Owing to their many fascinating features, MOFs have shown promising performances over conventional adsorbents in separation of gas mixtures. 7,[22][23][24][25][26] Both experiments 27 and computational methods 28,29 have demonstrated that the introduction of polar functional groups in the frameworks significantly enhances the CO 2 adsorption capacity of MOFs. Moreover, MOFs with coordinatively unsaturated metal sites have been shown to adsorb increased amounts of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid energy-intensive CO 2 capture, we have to resort to physisorptive processes (enthalpy of adsorption, Qo40 kJ mol À 1 ) rather than chemisorptive ones (Q440 kJ mol À 1 ) (ref. 29). Physisorption, however, brings new challenges.…”
mentioning
confidence: 99%